Associations Between Masculine Norms and Health-Care Utilization in Highly Religious, Heterosexual Men. Issue 3 (June 2019) - Novak, Josh R.; Peak, Terry; Gast, Julie; Arnell, Melinda
The purpose of this study was to use focus groups to explore married men's avoidance of health-care utilization. Five focus groups of 8 to 10 married, heterosexual, male participants ( N = 44) were conducted and analyzed using grounded theory methods. Several important themes emerged connected to how masculine norms were associated with health-care utilization at several domains including at the organizational level ( perceptions of doctors ), interpersonal level ( past family context and current family context ), and individual level ( illness severity, money concerns ). These themes were all connected with the societal theme of masculine norms, where men's reasons for health-care utilization (or underutilization) seemed in large part to emerge because of their perceptions of male gender roles. Implications for married men's health-care utilization and health prevention education will be discussed.